Peran Guru PPKn Mengembangkan Kecerdasan Moral Siswa MTs Raudlatul Hasaniyah Kota Probolinggo - Fitria Eka Ramadhan; Uswatun Hasanah; Ani Sulianti (CV. ITTC INDONESIA, 2024)
Teachers have an important role as learning agents who can inspire their students to make a difference and improve their moral intelligence. This study aims to (1) describe the role of civics teachers in developing students' moral intelligence at MTs Raudlatul Hasaniyah. (2) To describe the ways and solutions of civics teachers in planning, implementing, and evaluating learning to develop students' moral intelligence at MTs Raudlatul Hasaniyah. This research was conducted using a qualitative descriptive approach. The subjects of this research were Civics teachers, principals and the objects of research were students in grades VII, VIII and IX at MTs Raudlatul Hasaniyah who were taken randomly from each class totaling 13 students. The data collection technique used was observation, interview, and documentation methods. The data analysis techniques used are data reduction, data presentation, and verification or inference. The role of teacher is very influential on the implementation of education as an educator, the role of teacher as a manager, the role of teacher as a leader, the role of teacher as a facilitator, the role of teacher as an administrator, the role of teacher as an innovator, the role of teacher as a motivator, the role of teacher as a dynamicator. And students were also able to demonstrate moral competence through 4 aspects, namely integrity, responsibility, compassion, forgiveness. Encourage students to participate in extracurricular programs or policies as a place to develop moral intelligence, especially in the form of attitudes.